Improving The Professionalism Of Waiter And Waitress In Supporting The Succesaful Operational Food And Beverage Service At Aryaduta Hotel Medan - Elisa Br Tarigan; Dewi Shinta Wulandari Lubis (SEAN Institute, 2024)
The aim of this research is to find out the role of waiter and waitress in supporting the succses of food and drinks. The type of research used is qualitative research. In this research, data was collected through observation and in-depth interviews. The research sample was the manager the Aryaduta Medan Hotel in the Food And Beverage section. The results of this research show that standart operating procedures (SOP) greatly influence the profesionalism of waiters and waitress. With the presence of SOP, staff can function well at work.